Tiny monsters : the strange creatures that live on us, in us, and around us - Jenkins, Steve; Page, Robin (Boston : Houghton Mifflin Harcourt, 2020)
Did you know you share your home with monsters?! In this book explore the menagerie of tiny and unusual creatures--arthropods (insects, mites, and spiders)--found in our lawns and gardens, our food, our beds, our clothes, and even our eyelashes. Some of these monsters are so tiny that they were barely recognized, even by scientists, until the invention of the electron microscope. Although they may seem like aliens from another planet, these miniscule creatures live right alongside us. And just about all of them are harmless--and some are even helpful!
Includes bibliographical references.
Keywords: Insects -- Juvenile literature; Organisms -- Juvenile literature; Arthropoda -- Juvenile literature